Uropathogenic Infections Among Patients with Diabetes in Baghdad City - Kassim Khalil, Zena (Iraqi Journal of Science, 2023)
One hundred thirty four urine samples were collected from diabetic patients during the period from March –November -2014. From these samples there were 62.7% positive samples, women represented 45.3% and men represented 54.7% , some of them were a symptomatic as women represented 60.5% and men represented 58.7% and some were with clinical symptoms with or without a history of UTI. Hypertension diabetic women represented 45% and men represented 26% .Men suffering from prostate enlargement were represented 35% from the total diabetics .The E.coli isolates were represented 28.6% from the total cases ,Klebsiella spp isolates represented 20%, S. aureus isolates represented 16.7%,Proteus spp isolates represented 15.5% followed by Streptococcus fecalis isolates represented 13% and Candida albicans isolates represented 6.2%.Both gram positive and negative isolates were tested for their susceptibility and resistance to some common antibiotics, S.aureus isolates were resistant to ampicillin , cefotaxime and amoxicillin (71.4%,57%) respectively , Streptococcus fecalis isolates were resistant to erythromycin 82% and susceptible to ampicillin 73% , E.coil isolates were resistant to cloramphenicol 58% and susceptible to ciprofloxacin 83% . Klebsiella spp isolates were susceptible to ciprofloxacin and gentamicin both (100%) ,Proteus spp isolates were susceptible to norfloxacin 92%.